Static and Dynamic Performance Evaluation of Three-Wheeled Vehicle Frames Based on Aluminum and High-Grade Steel Using Finite Element Simulation - Yuzif, Rahman; Andiyanto, Andiyanto; priwintoko, baharudin (Akademi Inovasi Indonesia, 2025)
The increasing demand for energy efficiency and lightweight transportation has encouraged the development of three-wheeled vehicles with optimized structural frames. This study evaluates the static and dynamic performance of three-wheeled vehicle frames using three high-performance materials Aluminium 7075-T6, S690 steel, and ASTM A572 HSLA 60 steel. Finite Element Analysis (FEA) was conducted with Altair HyperWorks to analyze stress distribution, deformation, safety factor, and natural frequency response. Static analysis results indicate that all materials are structurally safe, with S690 steel showing the highest stiffness and safety factor, while Aluminium 7075-T6 provides the greatest strength-to-weight efficiency despite higher deformation. ASTM A572 HSLA 60 offers moderate performance as a cost-effective alternative. Modal analysis reveals similar natural frequency ranges (1.5–3.2 Hz) across all materials, indicating that dynamic behavior is more influenced by geometry than material properties. The findings highlight the trade-off between strength, stiffness, and weight, suggesting Aluminium 7075-T6 as the optimal choice for lightweight and energy-efficient applications, while S690 steel is preferable for heavy-duty requirements. Overall, this research emphasizes a holistic approach in material selection for three-wheeled vehicle frames to balance mechanical strength, vibration characteristics, and energy efficiency.